(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
It provides a detailed and thorough analysis of the pragmatic functions that discourse markers played in O. Henry’s well-known short stories, “The Gift of the Magi,” “The Last Leaf,” and “The Ransom of Red Chief.” It deals with analysis of how discourse markers help organize and guide narrative, and contribute to the way it is structured and to the development of a story. It also studies how they serve as an indicator, and how they signal emotional shifts, illustrate the contrast, and establish a stylistic coherence. Furthermore, the article points out how these markers serve to demonstrate the psychology of character, establish a narrative tone and reflect the author’s style through the role of discourse markers, and also point out this way of writing. By a close analysis of the interaction between language features and narrative function, this investigation shows how O. Henry strategically uses discourse markers for his purposes and in the course of both reading and writing texts for maximum impact on readers.